THE DETERMINANTS OF WOMEN LABOUR FORCE PARTICIPATION IN SABAH - Margret Yap Man; Toh Pei Sung; Sharija Che Shaari (Malaysian Journal of Business and Economics (MJBE), 2024)
This study aims to identify the determinants of women’s labour force participation (WLFP) in Sabah. Despite government and NGO efforts to provide benefits to women, and an increase in WLFP rates, male labour force participation remains higher. The objective of this study is to identify the determinants of WLFP by examining the effects of education level, family considerations, and flexible working arrangements in Sabah. Specifically, it seeks to investigate the moderating effects of work-life balance, marital status, and occupation level on these factors and WLFP in Sabah. A quantitative approach was employed with a sample size of 127 women participating in the labor force in Sabah. The results, derived from multivariate analysis and PCA using SPSS, showed the demographic profile of respondents and descriptive statistics. Additionally, measurement model evaluations were generated through SmartPLS 4.0. The study found that education level, family considerations, and flexible working arrangements significantly affect WLFP. Furthermore, the moderating effect of work-life balance on the relationship between family considerations and WLFP was observed. Future research should emphasize the broader context of women’s labour force participation, particularly in Sabah.